Bodily ownership and agency sensations in a natural state - Souta Hidaka (Nature Portfolio, 2021)
Abstract Our bodily sensation is a fundamental cue for our self-consciousness. Whereas experimental studies have uncovered characteristics of bodily sensation, these studies investigated bodily sensations through manipulating bodily sensations to be apart from one’s own body and to be assigned to external, body-like objects. In order to capture our bodily sensation as it is, this questionnaire survey study explored the characteristics of bodily sensation using a large population-based sample (N = 580, comprising 20s to 70s age groups) without experimental manipulations. We focused on the sensations of ownership, the feeling of having a body part as one’s own, and agency, the feeling of controlling a body part by oneself, in multiple body parts (the eyes, ears, hands, legs, nose, and mouth). The ownership and agency sensations were positively related to each other in each body part. Interestingly, the agency sensation of the hands and legs had a positive relationship with the ownership sensations of the other body parts. We also found the 60s age group had a unique internal configuration, assessed by the similarity of rating scores, of the body parts for each bodily sensation. Our findings revealed the existence of unique characteristics for bodily sensations in a natural state.